If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + -42 = 18 Reorder the terms: -42 + 6s = 18 Solving -42 + 6s = 18 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 6s = 18 + 42 Combine like terms: -42 + 42 = 0 0 + 6s = 18 + 42 6s = 18 + 42 Combine like terms: 18 + 42 = 60 6s = 60 Divide each side by '6'. s = 10 Simplifying s = 10
| 9x-13=x+3 | | 0+0+0=36 | | 6s-5=8s-1 | | f(x)=x^3+6x^2+9x+1 | | Ab-3ab+4ab= | | 10x+3=4x-2 | | 4z/9-4=-2 | | n^2-9n=-14 | | 3.08*sqrt(x)+18.87=2.87*sqrt(x)+20.08 | | n^2-9=-14 | | T/3-8=9 | | 24-6x=4 | | -8+3x=-12+8 | | 34-5x=6-9x | | 35-7x=56 | | 5x+6=-22-2x | | 10+8=-6+9x | | X=3Xcubed+x | | 20-4x=-5 | | 60=6(4-26) | | 10w=7700 | | 2k^2=-14-16k | | 15-x=31 | | 24-8x=12 | | 4=2d+10 | | 4sin(x)=1.2 | | T/5-7=11 | | 7s+40=152 | | 5x/4-3/x=1/4 | | 3wx-3v=7x+7v | | 6x^2+8x-11=0 | | 4+x-2x+2=5 |